Influence of ghrelin on rat pituitary GH3 cell line proliferation - Chmielewska, Małgorzata; Andrusiewicz, Mirosław; Żbikowska, Aleksandra; Kątniak, Katarzyna; Sadowska, Agnieszka; Arasimowicz-Banaszak, Grażyna; Graczyk, Sławomir; Waśko, Ryszard; Kotwicka, Malgorzata (Journal of Medical Science, 2016)
Introduction. Human ghrelin is the endogenous ligand of the growth hormone secretagogue receptor type 1a (GHSR1a). It is suggested that ghrelin is involved in pituitary adenomas pathogenesis. There are inconsistent data regarding the effect of ghrelin on cell proliferation. In this study the outcome of ghrelin in the rat pituitary adenoma GH3 cell line on morphology and proliferation ratio was evaluated. The ghrelin receptor (Ghsr) mRNA expression in GH3 cell line was established as well, because it was found that heterogeneous expression pattern characterized physiological and pathological conditions of tissues of different origin.Material and Methods. Suitable experimental model pituitary tumor (rat GH3 cell line) was stimulated with ghrelin in the final concentrations 10–12 M, 10–9 M and 10–6 M. Reverse transcription followed by real time polymerase chain reaction was used for ghrelin receptor gene transcript detection. The morphology as well as cell cycle of those cells were analyzed using Axio Vert.A1 Microscope (Zeiss) and BD FACSCalibur™ flow cytometer (Beckton Dickinson), respectively. The percentages of cells in the G0/G1, S, G2/M cycle phases were evaluated using the ModFit™ software (Verity Software, Inc., USA). Results. Ghsr mRNA presence was confirmed in GH3 cells. Ghrelin did not affect conspicuously GH3 cells morphology, however the ghrelin-induced proliferation index increase was caused by both decline of G0/G1 phases cells count and increase those being in S+G2/M (p
Keywords: ghrelin; ghrelin receptor; proliferation; pituitary adenoma